2018
DOI: 10.5815/ijisa.2018.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Medical Image Processing Algorithms Implemented in CUDA running on GPU based Machine

Abstract: Abstract-This paper illustrates the design and performance evaluation of few algorithms used for analysing the medical image volumes on the massive parallel graphics processing unit (GPU) with compute unified device architecture (CUDA). These algorithms are selected from the general framework, devised for computer aided diagnostic (CAD) system. The CAD system used for analysing large medical image datasets are usually a pipeline processing that includes a variety of image processing operations. A MRI scanner c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Based on this table, it can be seen that the use of parallel programming with GPU CUDA can increase the speed significantly, being able to be 39.22 times faster than serial programming with a CPU. The results of this study are the results of Kalaiselvi et al [26] and Chang et al [33]. Improving image resolution also increases the execution time, but the speedup also increases.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Based on this table, it can be seen that the use of parallel programming with GPU CUDA can increase the speed significantly, being able to be 39.22 times faster than serial programming with a CPU. The results of this study are the results of Kalaiselvi et al [26] and Chang et al [33]. Improving image resolution also increases the execution time, but the speedup also increases.…”
Section: Resultssupporting
confidence: 78%
“…Kumar et al proposed a joint LSM and LBM-based approach for histogram thresholding in image segmentation [25]. Kalaiselvi et al presented medical image processing algorithms implemented in CUDA running on GPU-based Machines [26], and Huang and Li use CUDA to accelerate in parallel computation [27].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it requires 34.7 [32.4–36.8] seconds using the CPU to diffuse a 3D CT image of around 90 slices (see Table II). Yet, according to Kalaiselvi (2018), 71 anisotropic diffusion filters can be sped up by 1–2 orders of magnitude when they are implemented on a modern GPU (such as the NVIDIA QUADRO K5000). Furthermore, Wei et.…”
Section: Discussionmentioning
confidence: 99%
“…They have developed parallel programs for sorting the data and compared the performance with the sequential implementation and found that the reduced execution time with GPU implementation. T. Kalaiselvi et al have proposed Per-Pixel Threading (PPT) and Per-Slice Threading (PST) and implemented some of the advanced image pre-processing algorithms for accelerating the computer aided diagnosis (CAD) systems in MRI volume analysis [17]. Authors have collected the image dataset from Whole Brain Atlas (WBA) maintained by Harvard Medical School and used for testing purpose.…”
Section: Related Workmentioning
confidence: 99%